2015
DOI: 10.1016/j.cpr.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce college student drinking: State of the evidence for mechanisms of behavior change

Abstract: Interventions to reduce college student drinking, although efficacious, generally yield only small effects on behavior change. Examining mechanisms of change may help to improve the magnitude of intervention effects by identifying effective and ineffective active ingredients. Informed by guidelines for establishing mechanisms of change, we conducted a systematic review of alcohol interventions for college students to identify (a) which constructs have been examined and received support as mediators, (b) circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
139
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(155 citation statements)
references
References 83 publications
(163 reference statements)
8
139
0
8
Order By: Relevance
“…Based on cognitive dissonance theory (Festinger, 1957), Miller (1983) noted “… if a person perceives his or her behavior to be seriously discrepant with his or her beliefs, attitudes, or feelings, a motivational condition is created to bring about change in one or another of these elements so that consistency is restored” (p. 157). Despite the use of some attitude change techniques in MI, few studies have provided strong tests of attitude change as a mechanism of behavior change (Reid & Carey, 2015). Furthermore, the results of this study suggest that a brief motivational intervention that was designed to change norms was effective and those changes in norms are associated with changes in drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Based on cognitive dissonance theory (Festinger, 1957), Miller (1983) noted “… if a person perceives his or her behavior to be seriously discrepant with his or her beliefs, attitudes, or feelings, a motivational condition is created to bring about change in one or another of these elements so that consistency is restored” (p. 157). Despite the use of some attitude change techniques in MI, few studies have provided strong tests of attitude change as a mechanism of behavior change (Reid & Carey, 2015). Furthermore, the results of this study suggest that a brief motivational intervention that was designed to change norms was effective and those changes in norms are associated with changes in drinking.…”
Section: Discussionmentioning
confidence: 99%
“…A number of college student drinking interventions elicit changes in alcohol use outcomes by correcting overestimated descriptive norms (Carey, Scott-Sheldon, Carey, & DeMartini, 2007; Cronce & Larimer, 2011; Reid & Carey, 2015). The perception that one’s peers approve of heavy drinking behaviors (“injunctive norms”) has received less attention in the prevention and intervention literature, but shows promise as an intervention strategy for college student drinking.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, injunctive norms are amenable to change following even a brief statement describing the attitudes of peers (Prince & Carey, 2010). A recent review of college student drinking interventions identified six studies that measured injunctive norms as a potential mechanism of effect (Reid & Carey, 2015), but only one specifically targeted injunctive norms (Schroeder & Prentice, 1998). While this study did not show change in injunctive norms, Reid and Carey (2015) note that this may be due to the long follow-up (4–6 months) and single-item measure of injunctive norms that may have been insensitive to change.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations